Diversity, equity, and inclusion in strategic communications : becoming culturally proficient communicators - Bush, Lee (Professor of strategic communications); Lindsey, Karen (Professor of strategic communications) (New York, NY: Routledge, 2025)
"Taking a DEI-first approach, this book teaches students to become culturally proficient communicators by approaching diversity, equity, and inclusion (DEI) with intentionality in every aspect of strategic communications. Those who work in strategic communications play a powerful role in shaping public perceptions and thus have a crucial responsibility to understand and practice the principles of diversity, equity, and inclusion in their work. This book introduces students to DEI theories and concepts and guides them through applying these concepts to communications research, planning, and execution. Chapters in the book align with the courses and competencies most often taught in advertising and public relations programs. It also includes chapters on "Inclusive Leadership" and "Working with Diverse Teams," as students will need these competencies when working on group class projects and in preparing for internships. The concluding chapter on "Communicating for Social Change" allows students to look beyond advertising and PR as corporate-centered disciplines and expand their understanding of the power of communications to advocate for social justice and change. Ideal for students at the undergraduate level with relevance to graduate students as well, the book can be used as a stand-alone text in DEI communications courses, as a supplement to core advertising or public relations texts, or in modules in advanced communications courses. Online materials for Instructors include teaching tips, suggested discussions and activities, student assignments, sample quizzes, and video links. They are available at www.routledge.com/9781032533865"--
Introduction -- DEI Definitions, Theories, and Concepts -- Understanding and Reaching Diverse Audiences -- Centering DEI in Strategic Writing -- Vanessa Bravo -- Visual Storytelling: Reframing Diversity and Inclusion -- Michele Lashley -- Inclusive Digital and Social Media Strategies -- Qian Xu -- Designing Culturally Sensitive Research -- Integrating DEI into the Campaign Planning Process -- Working on Diverse Teams -- Inclusive Leadership -- Reputation Management and DEI -- Communicating for Social Change.
Keywords: Communication in organizations; Public relations; Advertising; Discrimination; Equality; BUSINESS & ECONOMICS / Public Relations